Compact pattern reconfigurable Yagi patch antenna - Sooksumrarn, P.; Krairiksh, M. (My University, 2011)
With the increasing requirement to mitigate the problems of interference between users and electronic jamming, a reconfigurable pattern antenna is one of the solutions to resolve the problems. To switch radiation pattern in azimuth plane around a flat antenna, a Yagi patch antenna operated at higher mode is proposed. A bidirectional pattern using higher mode square patch is used as a driven element and electromagnetic-coupling with a parasitic element serving as a reflector provides a unidirectional pattern. The radiation pattern can be switched by switching feed-probe positions. Simulations were carried out at 2.45 GHz to find appropriate dimensions and validated by measurements. © 2011 Engineers Australia.
Keywords: Azimuth plane pattern reconfigurable; Higher-mode Yagi patch antenna; Pattern reconfigurable antenna; Yagi patch antenna